Navigating Society 5.0: Unraveling the Dynamics of a People-Centric Super-Smart Society - Abdullah, Assyari; Jayus, Jayus; Yazid, Yasril; Sumaiyah, Sumaiyah; Khairi, Akmal; Edison, Edison; Astuti, Dwi Sutri; Mutasir, Mutasir (ARISTO, 2024)
Society 5.0: A People-centric Super-smart Society" is a book that explains the concept of society developed by the Japanese government, which puts forward advanced technology and human-machine collaboration to improve people's quality of life. The book is written by experts and practitioners from various fields, including technology, economics, social, and politics with the editors of Hitachi-UTokyo Laboratory (H-UTokyo Lab.), The University of Tokyo and Bunkyo-ku, Tokyo, Japan. Many authors have contributed to the writing of this book, including Toshihiko Koseki (former Executive Vice President, The University of Tokyo), Shinobu Yoshimura (Vice President, The University of Tokyo), Norihiro Suzuki (Vice President and Executive Officer, CTO, Hitachi, Ltd.), and Shinji Yamada (General Manager, Center for Exploratory Research,  Hitachi, Ltd.), Takashi Haga and Miho Sugimoto (the University of Tokyo's University Corporate Relations Department), Mayumi Fukuyama and Tomiko Kinoshita (the Hitachi RD Group's Technology Strategy Office) The book is an expicution of the results of an in-depth study of a long process of joint research laboratory between Hitachi and The University of Tokyo in 2018. This book is written in 8 separate chapters but becomes a complete unity to explain the phenomenon raised in the title of this book. This book was published for the first time through Springer Singapore in 2018 which can be accessed for free through the Springer Open website